2007
DOI: 10.1186/1744-9081-3-54
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal volume reduction in children with chromosome 22q11.2 deletion syndrome is associated with cognitive impairment

Abstract: BackgroundPrevious investigations of individuals with chromosome 22q11.2 deletion syndrome (DS22q11.2) have reported alterations in both brain anatomy and cognitive function. Neuroanatomical studies have reported multiple abnormalities including changes in both gray and white matter in the temporal lobe, including the amygdala and hippocampus. Separate investigations of cognitive abilities have established the prevalence of general intellectual impairment, although the actual extent to which a single individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 39 publications
5
52
3
Order By: Relevance
“…26 Second, we found a positive association between full-scale IQ and hippocampus volume across diagnoses, yet full-scale IQ did not relate to the local anatomy of the hippocampus. Previous studies demonstrated a positive association between hippocampal volume and IQ in typically developing children 67 and children with 22q11.2DS; 38 however, we have not replicated such an association. The specificity of the association between the hippocampus and IQ would be better evaluated in a more comprehensive study of total and regional brain volumes as well as white matter microstructure.…”
Section: Comparison To Structural Neuroimaging Studiescontrasting
confidence: 54%
See 2 more Smart Citations
“…26 Second, we found a positive association between full-scale IQ and hippocampus volume across diagnoses, yet full-scale IQ did not relate to the local anatomy of the hippocampus. Previous studies demonstrated a positive association between hippocampal volume and IQ in typically developing children 67 and children with 22q11.2DS; 38 however, we have not replicated such an association. The specificity of the association between the hippocampus and IQ would be better evaluated in a more comprehensive study of total and regional brain volumes as well as white matter microstructure.…”
Section: Comparison To Structural Neuroimaging Studiescontrasting
confidence: 54%
“…For children with 22q11.2DS, anxiety symptoms may in part be a result of abnormal modulation by the anterior hippocampus via direct pathways and indirectly via the vmPFC. This may be additive to abnormal anatomy 38,60 and hyperactivity of the amygdala. Further study of the amygdala and prefrontal structure and connectivity in the present data set would better inform this hypothesis.…”
Section: Anterior Hippocampus Contribution To Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…The 22q11.2 deletion mouse model displayed several differences that mirrored what has been found in human 22q11.2 deletion syndrome [139][140][141]. Specifically, the larger striatum, smaller cerebellum, and smaller amygdala in the mouse model are all consistently found in human patients.…”
Section: Recent Investigations (2010-14)mentioning
confidence: 66%
“…Neuroimaging studies of 22q11DS describe how cerebral alterations in the syndrome relate to schizophrenia (Chow, Zipursky, Mikulis, & Bassett, 2002;Zinkstok & van Amelsvoort, 2005). Individuals with 22q11DS display general structural brain abnormalities, including reduced total brain tissue, grey and white matter volumes (Eliez, Schmitt, White, & Reiss, 2000;Kates et al, 2001), increased ventricular and basal ganglia volumes (Eliez, Barnea-Goraly, Schmitt, Liu, & Reiss, 2002), decreased thalamic, hippocampal as well amygdala volumes (Bish, Nguyen, Ding, Ferrante, & Simon, 2004;Debbané, Schaer, Farhoumand, Glaser, & Eliez, 2006;Deboer, Wu, Lee, & Simon, 2007), and a reduction in cingulate grey matter density (Simon et al, 2005). In schizophrenic 22q11DS subjects compared to nonschizophrenic, further anatomical differences include decreased whole-brain total volume and total white matter and increased total and sulcal cerebrospinal fluid volume (van Amelsvoort et al, 2004).…”
Section: Introductionmentioning
confidence: 99%